The influence of institutional ownership, independent commissioners, dividend policy, debt policy, and firm size on firm value - Danang Choirul Umam; Imar Halimah (Priviet Social Sciences Journal, 2021)
This study aims to examine the effect of institutional ownership, independent commissioner, dividend policy, debt policy, and firm size on firm value. The dependent variable used in this study is firm value, while the independent variables are the Effect of Institutional Ownership, Independent Commissioner, Dividend Policy, Debt Policy, and Firm Size. The population in this study are manufacturing companies, especially in the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2012 - 2017. The sample in this study was selected using the purposive sampling method and obtained as many as 36 samples of observations. The analytical technique used in this research is multiple linear regression analysis. The results of this study indicate that the variables of institutional ownership and firm size have a negative effect on firm value, while the variables of independent commissioners, dividend policy, and debt policy have a negative effect on firm value.